Jumping with barbell load: Assessment of lower limb joint kinematics and kinetics during landing - Fritz, J.; Stallegger, J.; Fessl, I.; Schwameder, H.; Kröll, J. (Journal of Biomechanics, 2021)
Loaded jumps are commonly used to improve leg muscle power. However, the additional load during jump-landing might increase the potential for overuse injury. Therefore, the aims of this study were to evaluate the effect that barbell load has on lower limb joint kinematics and kinetics during jump-landing and to evaluate the effect of arresting the barbell load at flight apex prior to landing on joint kinematic and kinetic variables. Barbell-loaded squat jumps (20, 40, and 60 kg) were investigated during two jump-landing conditions: 1) barbell-loaded (landing with barbell load) and 2) barbell-arrested (barbell load arrested at flight apex prior to jump-landing). Lower body kinematics and joint kinetics were assessed during jump-landing. In the barbell-loaded jump-landing condition, joint angles at initial contact decreased with increasing barbell load. Knee and hip peak power decreased (knee: -38%; hip: -46%), while ankle joint work increased with increasing barbell load. Joint moments, powers and work were decreased in the barbell-arrested condition compared to the barbell-loaded condition. Barbell-loaded jump-landings do not pose increased demands on the knee and the hip joint compared to bodyweight only jump-landings, due to the load-based reductions in jump height and joint kinematic adaptions. However, ankle joint contribution in energy dissipation is increased, possibly resulting in an increased overuse injury risk at this joint. Arresting the barbell load at flight apex prior to jump-landing substantially reduces the joint kinetics, hence serving as valuable training tool for athletes returning to sport after injuries.